The Effect of Implementing 5E (Engagement, Exploration, Explanation, Elaboration, Evaluation) Oriented Learning Model of Human Nervous System toward Student’s Learning Outcome for Grade XI in Science Program SMA Negeri 8 Academic Year 2014/2015 - Aisyah Safitri; Meida Nugrahalia (Jurnal Pelita Pendidikan, 2015)
This research aims to determine the effect of 5E (Engagement - Exploration – Explanation –Elaboration – Evaluation) Learning Model toward student learning outcomes on humannervous system concepts. This research was conducted in SMA Negeri 8 Medan, academicyear 2014/2015. The method used in this study is quasi-experimental methods. The populationin this research is all grade XI science students SMAN 8 Medan with 5 (five) classes academicyear 2014/2015. From the population was taken 80 students as the sample by using randomsampling. They are students of class XI Science 3 (consist of 40 students) as an experimentalclass use 5E Learning Model, while the students of class XI IPA 4 (consist of 40 students) as acontrol use direct learning model. The early data be obtained from the average pretest thatvalue of 55.16 post-test from experimental class and control class 53.66. For posttest inexperiment class is 80.92 and control class is 74.33. After that tested by normality test,homogeneity test and hypothesis test. Based on data from result of research used to obtainis 3.88 and at 5% significance level of 1.991. Because t-test > t-table so theresults of this research indicate that there were significant difference toward leraning outcomebetween experimental class use 5E Learning Model and control class use direct learning modelon human nervous system concept.Keyword: 5E Learning Model, Learning Outcomes.